A novel method for constructing 3D void RVE elements and rapid homogenization of composite materials - Li, Xiangxi; Li, Mengze; Zhang, Fengyi; Kong, Fanrui; Yang, Di; Qu, Weiwei; Ke, Yinglin (Composite structures, 2025)
•A multi-section interpolation algorithm was proposed to generate 3D voids in composite materials.•An "inertia algorithm" was introduced to generate random fiber distributions with high-volume fractions.•The random fiber spacing was effectively controlled, preventing clustering and achieving high efficiency.•A multi-scale method was proposed to simplify the 3D RVE model and enable rapid homogenization.•The homogenization time was reduced to 6.7%, while accuracy exceeded 95%. This article provides a method for modeling large-scale three-dimensional (3D) void defect Representative Volume Elements (RVE) with high fiber volume fractions and performing rapid homogenization. A 3D multi-section void construction method based on the Ferguson curve is proposed, along with an “inertia algorithm” that obtains optimal fiber positioning by minimizing overall inertia, taking the influence of void positioning into account. This method enables the rapid generation of 3D void defect RVE models with high fiber volume fractions. A model simplification and rapid homogenization method based on a multi-scale approach is proposed, in which the RVE containing void defects is treated as a mesoscopic structure with fiber-resin and void regions considered as two microcosmic structures. The fiber-resin region is regarded as a new material, simplifying the initial fiber-resin-void three-phase model into a two-phase model of the new material and voids. The simplified model has only 9.2% of the initial mesh elements and a homogenization time of 6.7%, achieving rapid homogenization. The rapid homogenization method was validated using two existing void RVE models, revealing an accuracy of over 95% for the obtained elastic constants.